HUBUNGAN AKTIVITAS FISIK DENGAN RISIKO JATUH PADA LANSIA DI DESA MARGOAGUNG SEYEGAN SLEMAN YOGYAKARTA - , NUR ISNAINI MULYORINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: According to the Department of Health Sleman (2013), the number of elderly aged 60 years or older who visited the health center area Seyegan elderly neighborhood health center is the largest number in Sleman. Based on the results of the data collection summary families Seyegan District of Sleman Regency (2013) the number of elderly in the district of approximately 4500 Seyegan elderly. Based on IHC List Elderly in district area Seyegan number of elderly aged 60 years or more in the village of 450 elderly Margoagung the number of elderly women more. The number of elderly women more potentially lead to impaired balance figures are also high that the risk of falling under the influence of hormonal, psychological, anthropometric and muscle strength. Therefore, an effort to reduce the prevalence of the risk of falling is to see how far the activity of the elderly and connect it to the risk of falling. Objective: To determine the relationship of physical activity with the risk of falls in the elderly in the village of Sleman Yogyakarta Margoagung Seyegan. Methods: This study is a quantitative study with a cross-sectional design. Using a questionnaire as instrument and observation sheets. Subject numbering 212 people consisted of elderly men and women as much as 89 123 elderly aged> 60 years. Samples were taken at random cluster sampling technique. Analysis of data using correlation tests Somers'd. Results: Test Somers'd found that the value of significance (p) <0.001 shows that there is a relationship between physical activity with the risk of falling. Obtained from this test correlation value of -0.326. Conclusion: There is a relationship between physical activity with the risk of falls in the elderly in the village of Sleman Yogyakarta Margoagung Seyegan. -0.326 Correlation is weak and the strength of the correlation indicates the opposite direction ie the higher the physical activity, the lower the risk of falling that occurs